Finding Peace in Suffering: Religiosity-Based Meaning-Making among Muslim Middle-Aged and Older Adults with Chronic Illness - Rezaputra, Indira Ravly; Zahro Aisiyah, Yusanti; Marlina, Erli (Faculty of Psychology, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
Chronic illness generates not only physical suffering but also profound existential challenges, particularly among middle-aged and older adults. Within Muslim communities, religiosity often serves as a central framework for interpreting and coping with suffering. This study explores how Muslim middle-aged and older adults living with chronic illness construct religiosity-based meaning to foster self-acceptance and psychological adaptation. Integrating Pargament’s Religious Coping Theory, Frankl’s Logotherapy, and Park’s Meaning-Making Model, this study employed an Interpretative Phenomenological Analysis (IPA) approach with ten participants aged 35–75 diagnosed with various chronic conditions. Semi-structured interviews were thematically analyzed. Four major themes emerged: (1) Divine Attribution, viewing illness as part of God’s will; (2) Self-Acceptance through Surrender; (3) Spiritual Coping through prayer, religious practices, and medical adherence; and (4) Holistic Well-Being, where faith supports resilience and meaning reconstruction. A Religiosity-Based Meaning-Making Model is proposed, highlighting the central role of Islamic faith in promoting psychological well-being.